Uji Ekstrak Daun Maja (Aegle marmelos L.) terhadap Pertumbuhan Bakteri Escherichia coli dan Staphylococcus aureus - Deny Romadhon Badaring; Sari Puspitha Mulya Sari; Satrina Nurhabiba; Wirda Wulan; Sintiya Anugrah Rante Lembang (Indonesian Journal of Fundamental Sciences, 2020)
Aegle marmelos L. is one of the tropical plants that has many benefits and also has the potential to be used as herbal medicines. It caused in some areas in Indonesia, A. marmelos have been widely used in traditional medicine. This research was a qualitatively descriptive study to see the effectiveness of A. marmelos leaf extract in inhibiting the growth of Escherichia coli and Staphylococcus aureus bacteria. Stages of A. marmelos leaf extract inhibition test on bacterial growth included the stages: extraction by maceration method, phytochemical test, chromatography test, anti-microbial test. Data were analyzed qualitatively. The results showed that A. marmelos leaf extract was more effective in inhibiting the growth of E. coli bacteria than in S. Aureus bacteria. This can be information that Maja leaf extract can be used as a phytopharmaca material for diseases caused by E.coli